2004
DOI: 10.1152/ajpcell.00198.2003
|View full text |Cite
|
Sign up to set email alerts
|

Volume changes and whole cell membrane currents activated during gradual osmolarity decrease in C6 glioma cells: contribution of two types of K+ channels

Abstract: Ordaz, B., L. Vaca, R. Franco, and H. Pasantes-Morales. Volume changes and whole cell membrane currents activated during gradual osmolarity decrease in C6 glioma cells: contribution of two types of K ϩ channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…K 1 conductance is also activated in these cells during IVR with different osmolarity thresholds in the presence or absence of Ca 21 (Ordaz et al, 2004). In a variety of cell types, gradual changes in osmolarity activate taurine efflux with different efflux threshold Souza et al, 2000;Ordaz et al, 2004). The lowest efflux is observed in cerebellar granule neurons where taurine efflux increases significantly at osmolarity reductions of only 2 mOsm (Fig.…”
Section: Isovolumetric Regulationmentioning
confidence: 88%
See 2 more Smart Citations
“…K 1 conductance is also activated in these cells during IVR with different osmolarity thresholds in the presence or absence of Ca 21 (Ordaz et al, 2004). In a variety of cell types, gradual changes in osmolarity activate taurine efflux with different efflux threshold Souza et al, 2000;Ordaz et al, 2004). The lowest efflux is observed in cerebellar granule neurons where taurine efflux increases significantly at osmolarity reductions of only 2 mOsm (Fig.…”
Section: Isovolumetric Regulationmentioning
confidence: 88%
“…This point should be clarified in light of new findings regarding the LCRR8 family members as integral elements of VRAC. K 1 conductance is also activated in these cells during IVR with different osmolarity thresholds in the presence or absence of Ca 21 (Ordaz et al, 2004). In a variety of cell types, gradual changes in osmolarity activate taurine efflux with different efflux threshold Souza et al, 2000;Ordaz et al, 2004).…”
Section: Isovolumetric Regulationmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies have suggested that volumesensitive taurine efflux does not always utilize anion channels. It is apparent that taurine efflux in Ehrlich Ascites cells [7], lactating rat mammary tissue [8,9], skate erythrocytes [23], supraoptic glial cells [24], C6 glioma cells [25] and cultured human intestinal epithelial cells [26] is independent from volume-activated chloride channels. It is also claimed that volume-activated taurine efflux from some cell types is via an anion exhanger [27].…”
Section: Discussionmentioning
confidence: 99%
“…see [64]). However, Ordaz et al [65] have shown that C6 glioma cells, exposed to a gradual change in the external osmolality, require a larger decrease to stimulate the release of taurine compared to that required to stimulate an increase in Cl -permeability. Similarly, Tomassen et al [29] have shown that activation of swelling-induced taurine release from cultured human intestinal cells required the medium osmolality to be lowered to 225 mosmoles/kg whereas volume-sensitive I -efflux was activated at 290 mosmoles/kg.…”
Section: Evidence In Support Of Separate Volume-activated Taurine Andmentioning
confidence: 99%